2018
DOI: 10.1089/thy.2018.0151
|View full text |Cite
|
Sign up to set email alerts
|

Persistent/Recurrent Differentiated Thyroid Cancer: Clinical and Radiological Characteristics of Persistent Disease and Clinical Recurrence Based on Computed Tomography Analysis

Abstract: With regard to cervical locoregional recurrence of DTC, active surveillance may be favored because more than a half of the cases are structurally persistent and stable. However, meticulous evaluation is necessary to detect progressive persistence and clinical recurrence, considering various clinical factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
9
0
2
Order By: Relevance
“…However, as the average time to recurrence has been reported to range from 6 months to several decades 4,13,14 , several studies have accepted that PD is also a factor in recurrence 8,12 . The following factors are associated with the risk of recurrence (without structural disease) after initial surgery: lymph node metastasis, histological findings, tumor size, extrathyroidal and extranodal 8,12 . We found that PD developed in 67.3% of patients who did not undergo neck dissection, strongly suggesting that improvements in preoperative CT assessment and initial surgery are essential.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, as the average time to recurrence has been reported to range from 6 months to several decades 4,13,14 , several studies have accepted that PD is also a factor in recurrence 8,12 . The following factors are associated with the risk of recurrence (without structural disease) after initial surgery: lymph node metastasis, histological findings, tumor size, extrathyroidal and extranodal 8,12 . We found that PD developed in 67.3% of patients who did not undergo neck dissection, strongly suggesting that improvements in preoperative CT assessment and initial surgery are essential.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, all reoperations performed after initial therapy are considered to reflect recurrence. However, as the average time to recurrence has been reported to range from 6 months to several decades 4 , 13 , 14 , several studies have accepted that PD is also a factor in recurrence 8 , 12 . The following factors are associated with the risk of recurrence (without structural disease) after initial surgery: lymph node metastasis, histological findings, tumor size, extrathyroidal and extranodal extensions, sex, and age at diagnosis 2 , 9 11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgery and postoperative thyrotropin suppression therapy or radionuclide therapy (I 131 ) are currently the standard treatment for DTC (Haugen et al, 2016). However, approximately 30% of these patients will relapse after the standard treatment (Kim et al, 2018b). The recurrent DTC tends to lose the ability to absorb iodine, thereby losing the option of radioactive iodine therapy.…”
Section: Introductionmentioning
confidence: 99%